2017
DOI: 10.1016/j.sysconle.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

On robust stability of switched systems in the context of Filippov solutions

Abstract: The stability problem of a class of nonlinear switched systems defined on compact sets with state-dependent switching is considered. Instead of the Carathéodory solutions, the general Filippov solutions are studied. This encapsulates solutions with infinite switching in finite time and sliding modes in the neighborhood of the switching surfaces. In this regard, a Lyapunov-like stability theorem, based on the theory of differential inclusions, is formulated. Additionally, the results are extended to switched sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…[27] proposed the application of Filippov's method to the small‐signal analysis of the general DC‐DC converters, and [28] first attempted sets with large periodic input for the same. Nevertheless, from a mathematical perspective, further theoretical study of Filippov's methods is required [29]. Thus, there still exists some practical difficulties for equilibrium point control.…”
Section: Introductionmentioning
confidence: 99%
“…[27] proposed the application of Filippov's method to the small‐signal analysis of the general DC‐DC converters, and [28] first attempted sets with large periodic input for the same. Nevertheless, from a mathematical perspective, further theoretical study of Filippov's methods is required [29]. Thus, there still exists some practical difficulties for equilibrium point control.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, SASs are represented by discontinuous right-hand side differential equations regarded as differential inclusion, in which a sliding mode may be occurring depending on the switching algorithm. It has been shown that the solutions to mentioned differential inclusion exist in the sense of Filippov, if the set-valued functions representing the differential inclusion are bounded, closed, convex, nonempty, and upper semicontinuous everywhere on the defined regions (Ahmadi et al, 2017). Continuous-time SASs have been studied from different aspects of control theory including both theoretical and practical cases.…”
Section: Introductionmentioning
confidence: 99%
“…In general, switched linear systems (SLSs) are mainly composed of individual subsystems and the switched rules coordinating these subsystems. The structure properties of SLSs have been investigated by many researchers, and some efforts have been expended on controller design (Sun and Duan, 2019; Sun and Ge, 2005; Zhao and Hill, 2008; Zong et al, 2016) and stability analysis (Ahmadi et al, 2017; Baleghi and Shafiei, 2016; Kundu and Chatterjee, 2016; Sun and Wang, 2012; Zhang et al, 2015). For the identification of SLSs with Box and Jenkins models, there exist several crucial issues to be addressed, including mode detection (MD) and parameter identification (PI).…”
Section: Introductionmentioning
confidence: 99%